2022
DOI: 10.3389/fonc.2022.834934
|View full text |Cite
|
Sign up to set email alerts
|

New Advances in Nano-Drug Delivery Systems: Helicobacter pylori and Gastric Cancer

Abstract: With the development of materials science and biomedicine, the application of nanomaterials in the medical field is further promoted. In the process of the diagnosis and treatment of diseases, a variety of drugs need to be used. It is an ideal state to make these drugs arrive at a specific location at a specific time and release at a specific speed, which can improve the bioavailability of drugs and reduce the adverse effects of drugs on normal tissues. Traditional drug delivery methods such as tablets, capsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Curcumin in combined therapy had synergistic effects and caused a more significant H. pylori reduction effect (Ranjbar and Mohammadi 2018 ). Nanocarriers could protect antibiotics in harsh gastric environments (Zhu et al 2022 ). As for the treatment for H. pylori , oral drug nanocarriers own advantages in dealing with the harsh acidified environment in the stomach and the hard to reach residence site of the pathogen (Zhang et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin in combined therapy had synergistic effects and caused a more significant H. pylori reduction effect (Ranjbar and Mohammadi 2018 ). Nanocarriers could protect antibiotics in harsh gastric environments (Zhu et al 2022 ). As for the treatment for H. pylori , oral drug nanocarriers own advantages in dealing with the harsh acidified environment in the stomach and the hard to reach residence site of the pathogen (Zhang et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of natural drugs, many factors limit its basic research and clinical transformation. In preclinical studies, various natural agents failed due to its poor bioavailability or activity, which could be solved by modifying their structures or dosage form (Roviello et al, 2019; Zhu, Su, et al, 2022a). Previous clinical evidence has demonstrated that few natural compounds triggered apoptosis of GC cells in patients, such as paclitaxel, camptothecin, colchicine, and ginsenoside Rg3.…”
Section: Discussionmentioning
confidence: 99%
“…Drug-loaded NPs achieve their therapeutic effect via localized accumulation and sustained release. This postulates that the nanoparticle-based formulation of antibiotics is a good option for treating H. pylori [ [163] , [164] , [165] ]. Furthermore, when compared to direct antibiotic use, nanoparticular systems have imparted less toxicity in therapy, and these strategies play critical part in reducing antibiotic resistance.…”
Section: Strategies To Overcome the Drawbacks: Need For Novel Formula...mentioning
confidence: 99%